The Development of Moci Entrepreneurial in Sukabumi: A Case Study on the Factors Driving the Growth of Local Creative Industries - Mita Sonaria; Abdul Aziz Assayuti; Priyo Sasmito; Kurniawan; Yusuf Iskandar (West Science Journal Economic and Entrepreneurship, 2023)
Moci entrepreneurship is one of the main focuses in the development of creative industries in Indonesia. One area that shows great potential in the development of moci entrepreneurship is Sukabumi. This study aims to analyze the factors that drive the growth of the local creative industry in Sukabumi. The research method used was a case study by taking samples of a number of moci entrepreneurs in Sukabumi and conducting in-depth interviews to collect data. The results showed that factors such as government support, availability of quality human resources, networking and collaboration between creative industry players, as well as significant market interest and demand are important factors in encouraging the growth of moci entrepreneurship in Sukabumi. In conclusion, the development of moci entrepreneurship in Sukabumi is highly dependent on these factors. Therefore, government support and collaboration between local creative industry players need to be increased to accelerate the growth of the creative industry in Sukabumi and Indonesia as a whole.